Student’s Perceptions of English Learning Activities Using Video Media at Vocational School - Maulana, M Aziz; Rini, Setia (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This research explores the integration of video media in teaching English as a foreign language at SMKN 1 Salatiga. The study was conducted using a mixed-method approach, combining questionnaires and interviews to examine both implementation strategies and student perceptions. A total of 35 tenth-grade students participated. The findings show that video-based instruction contributes significantly to improved vocabulary comprehension, listening skills, and motivation. Students demonstrated high levels of agreement regarding the effectiveness of video media in supporting flexible, engaging, and self-directed learning. The data were supported by theoretical frameworks including Mayer’s Cognitive Theory of Multimedia Learning and Vygotsky’s Sociocultural Theory. Results also align with the principles of the Engagement Theory and Universal Design for Learning (UDL), reinforcing video’s role in enhancing interactivity and personalization in instruction. Overall, the study concludes that video media is a powerful tool for language development in vocational education settings. It is recommended that educators adopt diverse multimedia content to accommodate student needs and preferences in learning English more effectively.